PEMBIAYAAN BAGI HASIL: ANALISIS PENGARUH FAKTOR INTERNAL DAN FAKTOR EKSTERNAL BANK SYARIAH - Widawati, Exvita; Wildana, Muhammad Dandy Alif (Islamic Economics and finance in Focus, 2024)
The rapid development of the Islamic banking industry in Indonesia is evident in the substantial share of profit and loss sharing (PLS), particularly when compared to other nations. However, on regional scale, PLS as a primary product of Islamic banks has yet to assert dominance of disbursed financing. Analysis of internal and external factors that influence PLS of Islamic banks in Indonesia will be the focus of the research. The Error Correction Model method was chosen to determine the effects in the short and long term. Time series analysis was carried out in the time period January 2015 to December 2022. This research found that internal factors, Third-Party Funds had a positive and significant effect on PLS in the short and long term. Then Allowance for Impairment Losses in the short term does not have a significant effect but in the long term it has a negative and significant effect. Interestingly, PLS is not sensitive to CAR and economic growth. This research shows the resilience of Islamic banks in facing the crisis caused by the Covid-19 pandemic. PLS grew higher in the period after the Covid-19 Pandemic compared to before the Covid-19 Pandemic. The implications of these findings encourage Islamic banks to develop products and services, tighten risk management in the long term, and expand the market share of Islamic banks.